2000
DOI: 10.1364/josab.17.000919
|View full text |Cite
|
Sign up to set email alerts
|

High-average-power (>20-W) Nd:YVO_4 lasers mode locked by strain-compensated saturable Bragg reflectors

Abstract: High-average-power (>20-W) Nd:YVO-4 lasers mode locked by strain-compensated saturable Bragg reflectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…Our phenomenological model is consistent with the experimental observations made in [15]. In particular, as the temperature of the SA is increased, the intracavity power required to switch from QS-ML to cw ML increases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our phenomenological model is consistent with the experimental observations made in [15]. In particular, as the temperature of the SA is increased, the intracavity power required to switch from QS-ML to cw ML increases.…”
Section: Discussionsupporting
confidence: 89%
“…From an analysis of the change in threshold power, it was deduced that the SA introduces and additional 2.4% of loss to the cavity. At present, it is not clear why this background loss is so high -comparison with similar devices having one or two InGaAs quantum wells [15] would suggest this loss should be considerably lower. We confirmed that this loss is not the sum of saturable and nonsaturable losses of the SA, but only the passive non-saturable loss by tuning the absorption spectrum sufficiently to short wavelengths such that the saturable component is minimal.…”
Section: Discussionmentioning
confidence: 90%
“…The total spectral width was 41 GHz, measured using a scanning Fabry-Pérot interferometer. Similar results with output powers of about 20 W, albeit with pulse durations above 20 ps, have been reported earlier and can be found in the literature [13,14].…”
Section: Sesam Mode Locked Picosecond Nd:yvo 4 Oscillatorssupporting
confidence: 91%
“…12. A Strain-balanced doublequantum-well InGaAs/GaAsP saturable Bragg reflector [7,16] was used as the passive mode-locking element. The gain medium was placed away from the end of the cavity to avoid effects associated with spatial hole burning [17].…”
Section: Extension Of Operational Parameter Space Of Passively Mode-lmentioning
confidence: 99%